Clinical Observation on the Treatment of Macular Edema Secondary to Retinal Vein Occlusion by Liuzi Yangmu Wan Combined with Conbercept Ophthalmic Injection - Zhu, Jinyifu; Yang, Yurong; Lei, Xiaoqin (Journal of Contemporary Medical Practice, 2024)
To observe the effects of Liuzi Yangmu Wan combined with Conbercept Ophthalmic Injection in the treatment of retinal vein occlusion secondary to macular edema on the visual acuity and macular thickness of the patients, and to further clarify its clinical efficacy. Eighty patients diagnosed with retinal vein occlusion at Xi’an Fourth Hospital from July 2021 to July 2023, meeting the inclusion criteria, were randomly divided into two groups using a random number table method: the combination group (40 patients, 40 eyes, treated with Liuzi Yangmu Wan combined with intravitreal injection of Conbercept Ophthalmic Injection), and the control group (40 patients, 40 eyes, treated solely with intravitreal injection of Conbercept Ophthalmic Injection). Both groups followed a “1+PRN” treatment regime based on the patient’s condition. Best corrected visual acuity (BCVA) and central macular thickness (CMT) were recorded before treatment and 3, 6 months after treatment, as well as the recurrence rate and number of anti-VEGF injections administered. Before treatment, there was no statistically significant difference between the two groups in BCVA and CMT (P > 0.05). Three months after treatment, compared to before treatment, the BCVA in the combination group improved from 0.81 ± 0.51 to 0.49 ± 0.28 (P < 0.05), and in the control group it improved from 0.79 ± 0.41 to 0.51 ± 0.34 (P < 0.05). The CMT in the combination treatment group decreased from 603.92 ± 249.51μm to 434.90 ± 157.81μm (P < 0.05), and in the control group, it decreased from 595.20 ± 185.93μm to 464.25 ± 122.69μm (P < 0.05), with a significant difference between the two groups (P < 0.05). During the follow-up period, no adverse reactions were observed in any of the patients. The number of injections during the observation period was lower in the combination group (2.15 ± 0.58) compared to the control group (2.63 ± 0.66). Liu Zi Yang Mu Wan is safe and effective in treating retinal vein occlusion, capable of improving patients’ vision, accelerating the resolution of macular edema, and promoting the absorption of hemorrhages. From this, it can be concluded that the combination of Liuzi Yangmu Wan and Conbercept is more effective than the sole use of Conbercept, and it can reduce the number of intravitreal injections needed.